Sarkasme pada Tanggapan Warganet di Platform Tiktok dalam Konteks Pemilihan Kepala Daerah Provinsi Gorontalo Tahun 2024 - Moh. Fadil Sunge; Ulfa Zakaria; Nuramila Nuramila (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study examines sarcastic utterances by netizens on TikTok during the 2024 Gorontalo Regional Election, focusing on their forms, functions, and influencing factors. The research analyzed comments on TikTok videos related to the election, specifically those containing sarcasm, selected purposively. Using a qualitative descriptive approach, the study categorized sarcastic utterances into four forms: (1) action sarcasm, (2) trait sarcasm, (3) result-of-action sarcasm, and (4) advisory sarcasm. The functions of these utterances include expressing opinions, prohibition, information, emphasis, rejection, commands, and statements. The study also identified two main factors influencing the use of sarcasm: emotional outbursts and disappointment toward the candidate pairs. The findings suggest that sarcasm is employed as a medium for expressing attitudes, emotions, and political judgments in digital discourse. This research highlights the role of sarcastic speech acts in the political conversation on social media during election campaigns.